Avaliação de genótipos de cártamo quanto ao desempenho agronômico, divergência genética e produtividade da água - Zoz, Tiago [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The concept water productivity in agriculture is the relation between the yield of crop and the water quantity required to get that yield. Water is a valuable resource for agriculture; therefore, it is interesting to adopt crops with higher yield capacity and requires lower water quantity. Safflower (Carthamus tinctorius L.) is an oil crop that is getting highlight in last years, mainly due its high oil content of high quality and drought tolerance. However, safflower is an underexplored commercially crop in Brazil and due it, there are few studies about plant breeding and drought tolerance. This study aim to evaluate the agronomic performance, water productivity and the genetic divergence in safflower cultivars imported from United States in crop conditions of Brazil. In addition, this study aim to evaluate the water productivity of high oleic safflower genotypes under different water depth. The study was composed by two trials. The first trial, related to agronomic performance and genetic divergence of American cultivars in crop conditions of Brazil was run in Sao Manuel, SP, from April to September of 2012. The experimental design was randomized blocks with four replications. It were evaluated 12 safflower cultivars imported from United States. From the data of grain and oil yield it was estimated the water productivity in relation to grain and oil. It were estimated the genetic correlation coefficients, and from them, it were estimated the direct and indirect effects of traits evaluated on grain yield and oil yield by path analysis. The genetic divergence analysis between cultivars was performed by multivariate analysis technique of principal components analysis (PCA). The second trial, related to water productivity of high oleic safflower genotypes under different water depth was run in Lubbock - TX, United States, from May to October of 2013. The experimental design was randomized blocks with ...

O conceito de “produtividade da água” aplicado na área agrícola diz respeito a relação entre a produção de determinada cultura e a quantidade de água requerida para atingir essa produção. Sabendo que a água é um recurso cada vez mais valioso para a agricultura, é interessante a adoção de culturas com maior capacidade produtiva utilizando menores quantidades de água. O cártamo (Carthamus tinctorius L.) é uma espécie oleaginosa que vem ganhando destaque nos últimos anos, principalmente devido ao seu elevado teor de óleo de alta qualidade presente em seu grão e a tolerância a deficiência hídrica. No entanto, no Brasil o cártamo ainda é pouco conhecido, sendo escassoz os estudos voltados ao melhoramento genético e tolerância à deficiência hídrica dessa cultura. O objetivo neste estudo foi avaliar o desempenho agronômico, a produtividade da água e a divergência genética de cultivares de cártamo provenientes dos Estados Unidos nas condições de cultivo do Brasil e também avaliar a produtividade da água de cinco genótipos de cártamo alto-oleicos sob diferentes lâminas de água. O estudo foi composto por dois experimentos. O primeiro experimento, relacionado ao desempenho agronômico, produtividade da água e divergência genética de cultivares norte-americanas nas condições de cultivo do Brasil foi conduzido no município de São Manuel, SP, entre os meses de abril e setembro de 2012. O delineamento experimental adotado foi o de blocos ao acaso com quatro repetições e os tratamentos constituídos por 12 cultivares de cártamo provenientes dos Estados Unidos. A partir dos dados de produtividade de grãos e de óleo estimou-se a produtividade da água em relação a grãos e a óleo. Foram estimados os coeficientes de correlações genéticas e a partir destes estimou-se os efeitos diretos e indiretos das características avaliadas sobre a produtividade de grão ...
Evaluation of safflower genotypes to agronomic performace, genetic divergence and water productivity
Keywords: Analise multivariada; Plantas oleaginosas - Melhoramento genético; Irrigação agricola; Oilseeds